Analysis of the crack-crack interaction effect initiated in aeronautical structures and repaired by composite patch - Nour Chafak Mohamed Ibrahim; Serier Boualem,; Mechab Belad (Fracture and Structural Integrity)
In this work, we analyze three - dimensionally, by the finite element method, the performance of the repair of aeronautical structures damaged by cracking and repaired by patch of composite materials. The effect of crack-crack interaction according to their position and interdistance was analyzed. The criterion of rupture retained for this study is the factor of intensity of constraints. We show that this factor increases considerably and reaches a critical threshold when the two cracks develop towards each other. The repair of such damage using a composite patch ensures the stability of this structure during the commissioning process. The sharp fall in the stress intensity factor is characteristic of this stability